Quality Improvement of Health Plaster Products With Six Sigma Method and QCDSME Analysis - Nur Janah, Ragillia Fitri; Wahyuni, Hana Catur; Marodiyah, Inggit (Universitas Ahmad Dahlan, 2024)
Health plasters are one of a pharmaceutical company's excellent items. There are still defective products in the manufacturing process, including torn paper, joint 1, not cut, perforated edges, joint 2, tucked, long-short, and asymmetrical. Research conducted between June and December 2021 reveals that 192.960 Kg of substandard items were discovered. The contribution of this research is to identify the underlying reasons of the problem and decrease the number of product faults. By using the QCDSME (Quality-Cost-Delivery-Safety-Morale) method analysis in the cost stage, this company is known to experience losses due to defective products of IDR 18,047,232 / year. The results of the analysis using the six sigma method at the analyze stage using the fishbone diagram tool are known that defective products are caused by the absence of size standards in the repair of plate and pressure roll positions, differences in operator responses, the absence of written procedures for handling product defects, and the existence of product roll rolls that are too loose or tight. The improvement proposal made next is to make a size standard for the plate position with a value of 12.5 ± 1 cm and a pressure roll with a value of 22 ± 1 mm with additional tools in the form of a ruler. After taking corrective steps and quality control on product defects, the results showed that the value of product defects decreased from the previous average of 1,119 pcs/day to 205 pcs/day, so that the company's loss value was reduced to IDR 3,306,240/year.